Increasing Productivity And Profit Of Irriged Rice Farming With Legowo Row Planting System - Alfayanti Alfayanti; Djhon Firison; Ratini Ratini; Andi Ishak; Harwi Kusnadi; Emlan Fauzi (UNIVED Press, Dehasen University Bengkulu, 2022)
This study aims to analyze the differences in productivity and income of lowland rice farming between the jajar legowo 2:1 cropping system and the tiled planting system. The research was conducted from April to July 2021 in the Women Farmers Group Payau Indah, Manggul Village, Manna District, South Bengkulu Regency. Data was collected by means of observation and interviews with farmers implementing demonstration plots for rice cultivation with an area of ​​0.024 ha which was divided into two experimental plots with an area of ​​0.012 ha each. The first plot uses a 2:1 row legowo planting system and the second plot uses a tile planting system. The data collected is data on productivity and farm income from the two experimental plots. Data analysis was done descriptively. The results showed that the jajar legowo planting system resulted in higher productivity and farm income than the tile planting system